Lentivirus-Mediated Knockdown of Tumor Protein D52-like 2 Inhibits Glioma Cell Proliferation - Wang, Z.; Sun, J.; Zhao, Y.; Guo, W.; Lv, K.; Zhang, Q. (Cellular and Molecular Biology, 2014)
TPD52L2 (tumor protein D52–like 2) is a member of TPD52 family which has been implicated in multiple human cancers. Recently, TPD52 protein was shown to be associated with several malignancies, but very little is known about the function of TPD52L2 in cancers, especially in glioma to date, and its roles in glioma occurrence and progression remain to be elucidated. In the present study, we employed lentivirus-mediated RNA interference (RNAi) to knock down TPD52L2 expression in human glioma cell line U251. We found that knockdown of TPD52L2 significantly not only inhibited cell proliferation and colony formation, but also induced G0/G1 cell cycle arrest in vitro. Taken together, these findings suggest that TPD52L2 might play an important role in glioma tumorigenesis.